Invaded : [an Alienated novel] / Melissa Landers - Landers, Melissa
Cara and Aelyx maintain their extremely long-distance relationship, with Cara continuing as an exchange student and becoming human representative to a panel preparing for a human colony on L'eihr and Aelyx working on a campaign to improve human-L'eihr relations, which soon makes him a target of extremists.